Analisis Reaksi Pasar Modal Indonesia Terhadap Peristiwa Kenaikan Harga Bahan Bakar Minyak 21 Juni 2013 ( Studi Terhadap Saham ILQ 45 ) - , GAMAWAN RIZAL PAGHLEVI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this study is to analyze the abnormal return of stocks listed in Indonesia Stock Exchange represented by LQ 45 index and to determine whether there is any difference in the average abnormal return and trading volume activity before and after the anouncement of the increase in oil prices by the government of Indonesia on June 21, 2013. The database used in this research is secondary data of daily stock returns and daily trading volume. Analysis of abnormal returns and trading volume activity using data return and trading volume of the stock with a span of t - 7 until t +7 events. The results obtained in this study are the stock market, especially firms stock listed on LQ 45 index reacts to the announcement of the increase on oil prices. The reaction of capital market is shown by the t-test results that indicates there are significant abnormal returns around the announcement date of the increase in fuel prices. The reaction of capital market is also spotted in the differences in average trading volume activity that is significant in the period before and after the announcement, although there is no significant difference in the average abnormal return in the period before and after the announcement of fuel price increases.